Energy consumption, tourism, economic growth and CO2 emissions nexus in India. Issue 2 (3rd April 2021) - Jayasinghe, Maneka; Selvanathan, Eliyathamby A.
Abstract: India is one of the fastest growing nations in the world with ample scope for renewable energy. Nevertheless, challenges in expansion of renewable energy consumption have resulted in pollutant emissions continuing to be a noteworthy environmental concern in India. This paper investigates the relationship between energy consumption, CO2 emissions, Gross Domestic Product (GDP), and international tourist arrivals in India during 1991-2018, using the Autoregressive Distributed Lag and Vector Error Correction Model frameworks. This study extends the Indian literature on economic growth, energy consumption, and pollutant emissions nexus by including tourism, an energy-intensive industry in the model specification. Results reveal that energy consumption and tourism positively contribute to CO2 emissions. A long-run unidirectional causality running from energy consumption, GDP, GDP 2, and tourist arrivals towards CO2 emissions is observed. Our results suggest that sustainable tourism, energy consumption, and economic growth should be at the forefront of the economic development agenda of India.